READING COMPREHENSION QUESTIONS DEVELOPED BY ENGLISH TEACHERS OF SENIOR HIGH SCHOOLS IN SURABAYA - Mukhlisatun Muayanah (JURNAL SOSIAL HUMANIORA (JSH), 2014)
According to the Competence Based Curriculum (KBK) in the subject of English at Senior High School, the reading skill emphasizes the ability to read written English in the forms of narration, spoof/recount, procedures, report, news items (1st grade), anecdote, exposition, hortatory exposition (2nd grade), descriptions, explanation, discussion, and commentary  (3rd grade). Therefore, the objective of teaching reading is to enable the students to have the ability to comprehend and interpret the content of many types of written English discourse.